New Insights into the Exploitation of Vitis vinifera L. cv. Aglianico Leaf Extracts for Nutraceutical Purposes - Fabiana Labanca; Immacolata Faraone; Maria Rosaria Nolè; Ruth Hornedo-Ortega; Daniela Russo; Maria Carmen García-Parrilla; Lucia Chiummiento; Maria Grazia Bonomo; Luigi Milella (Antioxidants, 2020)
The leaves of Vitis vinifera L. have been used for a long time in traditional medicine for the treatment of many ailments. Grape polyphenols, indeed, have been demonstrated to be able to defend against oxidative stress, responsible for various disorders such as cancer, diabetes and neurodegenerative diseases. The effects of different extraction techniques, Soxhlet (SOX), Accelerated Solvent (ASE 40, ASE 50) and Ultrasound Assisted Extraction (UAE) were studied in this work to evaluate their impact on the chemical profile and bioactive potential of Vitis vinifera L. (cv. Aglianico) leaf extracts. The phytochemical profile was investigated by HPLC-DAD and 9 phenolic compounds were identified and quantified in the extract. Moreover, the antioxidant, anticholinesterase and antityrosinase activities were evaluated. In detail, the total polyphenol content and antioxidant activity (2,2-diphenyl-1-picrylhydrazyl, Oxygen Radical Absorbance Capacities and β-Carotene Bleaching assays) were evaluated and compared to assess the Relative Antioxidant Capacity Index (RACI). To test the inhibitory activity of extracts towards cholinesterases, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibition assays were performed. SOX and ASE 50 have shown the highest value of RACI, 0.76 and 0.65, respectively. Regarding enzymatic inhibitory activity, ASE 50 (IC50 = 107.16 ± 8.12 μg/mL) and SOX (IC50 = 171.34 ± 12.12 μg/mL) extracts exhibited the highest AChE and BChE inhibitory activity, respectively, while UAE (IC50 = 293.2 ± 25.6 μg/mL, followed by SOX (IC50 = 302.5 ± 38.3 μg/mL) showed the highest tyrosinase inhibition value. Our results demonstrated for the first time that Aglianico leaves are important sources of phenols that could be used to prevent oxidative stress and be potentially helpful in diseases treatable with tyrosinase and cholinesterase inhibitors, like myasthenia gravis or Alzheimer’s.